Issue Information. Issue 8 (28th August 2021) - Unknown
Abstract : Cover : In this issue, Reitz et al . describe a protocol for immunofluorescent labeling and imaging of four distinct antigens, without spectral or reagent crosstalk, using conventional fluorophores and a long Stokes‐shifted fluorophore. This combination allows for multiplexed imaging of the antigens in a single sample, with excellent spectral discrimination suitable for sensitive analyses using standard imaging hardware. In the cover image, three fluorophores with conventional Stokes shifts, here labeling GFAP (yellow), Iba1 (magenta), and CD68 (cyan), are combined with a long Stokes‐shifted fluorophore, here labeling synapsin (green). This combination offers a simple, rapid, low friction method to add a 4th molecular target of average‐to‐low abundance and antigenicity to standard immunofluorescence imaging. Image provided by Sydney J. Reitz.